2015
DOI: 10.1038/nmat4318
|View full text |Cite
|
Sign up to set email alerts
|

In situ NMR and electrochemical quartz crystal microbalance techniques reveal the structure of the electrical double layer in supercapacitors

Abstract: Supercapacitors store charge through the electrosorption of ions on microporous electrodes. Despite major efforts to understand this phenomenon, a molecular-level picture of the electrical double layer in working devices is still lacking as few techniques can selectively observe the ionic species at the electrode/electrolyte interface. Here, we use in situ NMR to directly quantify the populations of anionic and cationic species within a working microporous carbon supercapacitor electrode. Our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
283
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(299 citation statements)
references
References 32 publications
14
283
1
1
Order By: Relevance
“…We previously showed that charging in the positive electrode takes place by swapping of anions and cations (counter-ion -co-ion exchange mechanism, X = 0), while charging in the negative electrode occurs by counter-ion adsorption (X = +1, see Figure 3c inset). 5 As a result, for positive polarisations the total in-pore ion population shows only minor changes with voltage, while for negative polarisation a marked increase is observed (Figure 3c). This increase of in-pore ion population correlates with the reduction of D in-pore for both ions: i.e., it appears that increasing ion-ion interactions lead to a reduction of D in-pore with 7 voltage for negative polarisations.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…We previously showed that charging in the positive electrode takes place by swapping of anions and cations (counter-ion -co-ion exchange mechanism, X = 0), while charging in the negative electrode occurs by counter-ion adsorption (X = +1, see Figure 3c inset). 5 As a result, for positive polarisations the total in-pore ion population shows only minor changes with voltage, while for negative polarisation a marked increase is observed (Figure 3c). This increase of in-pore ion population correlates with the reduction of D in-pore for both ions: i.e., it appears that increasing ion-ion interactions lead to a reduction of D in-pore with 7 voltage for negative polarisations.…”
mentioning
confidence: 85%
“…Prior to charging, the electrode pores contain a large number of electrolyte ions, 15,19,20 and as a result charge storage is generally more complex than simple counter-ion adsorption (counter-ions are defined as having charge opposite to the electrode in which they are located). [5][6][7]15 A range of different charging mechanisms can operate …”
mentioning
confidence: 99%
“…The electrode materials, which is a key component of ECs [15], generally fall into three categories: (1) porous carbons with high specific surface area (e.g., metal-organic frameworks-derived nanoporous carbon [16,17], carbidederived carbon [18], carbon nanotubes [19], graphene [20]), (2) intrinsically conductive polymers (ICPs, e.g., polyaniline [21][22][23], polypyrrole [24,25], poly(DNTD) [26,27]), and (3) transition metal oxides/hydroxides (e.g., RuO 2 [28], MnO 2 [29], MoS 2 [30], Ni(OH) 2 [31], Co(OH) 2 [32]). Generally, porous carbons serve as electrode materials of electric doublelayer capacitors (EDLCs) to store energy via an electrostatic charge accumulation [33], while the ICPs and transition metal oxides/hydroxides serve as electrode materials of pseudocapacitors to store energy via redox reactions [34]. Actually, ICPs and their composites have received ever increasing attention because of their low cost, environmental friendliness, good redox reversibility, and high pseudocapacitance values [35,36].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The accessibility of the micropores of the as-prepared carbons to electrolytes was investigated using NMR spectroscopy, which is achieved by analysising the perturbation of NMR spectra of the electrolyte induced by the adsorbents. When the electrolytes are confined in a nanopore, the NMR peak for a nucleus shifts to a higher position due to the diamagnetic shielding effect of the sp 2 hybridized carbon networks [21]. Such effect is only appreciable when the pores are small enough (i.e.…”
Section: Figurementioning
confidence: 99%
“…Such effect is only appreciable when the pores are small enough (i.e. micropores) and thus the NMR technique can be used to probe the infiltration of ions into small pores [21][22][23][24]. Both HA-800 and CNF-800 were impregnated with an acetonitrile solution of EMIImBF4 and 11 B NMR spectra were acquired for the electrolyte-loaded carbons after evaporating the solvent and the results are shown in Figure 4.…”
Section: Figurementioning
confidence: 99%